The Holy Spirit in mission: prophetic speech and action in Christian witness - Tyra, Gary (IVP Academic, 2011)
"Would God that all the Lord's people were prophets": the biblical connection between the coming of the Spirit and prophetic activity -- "You shall receive power": the connection between prophetic activity and missional faithfulness -- "The Spirit bade me go": missional faithfulness and the growth of global Pentecostalism -- "Men of Athens!": becoming more missionally faithful in the West -- "A man named Ananias came to see me": encouraging missional faithfulness among the evangelical rank and file